Understanding and Implementing Self-Determination for Indigenous Peoples: The case of the Sami in Sweden - Fuchs, Léon (Linnéuniversitetet, Institutionen för samhällsstudier (SS), 2014)
The study focuses on the current status of the Sami indigenous community of Sweden and on the implementation of the concept of self-determination for indigenous peoples, as presented by the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) of 2007. Nowadays, even if the Sami community of Sweden can enjoy several political, economic, social and cultural rights, a lot remains to be done concerning the development of their self-determination because several international principles related to indigenous rights have not been implemented so far. Therefore, the aim of the study is to explore how the Sami people of Sweden define and understand the principle of self-determination for indigenous peoples and how they would like to implement it in the future, while also focusing on what can be learned from their particular situation from a conceptual perspective. To achieve that, the research has been mainly based on a field study carried out at the end of April 2014 and at the beginning of May 2014. Several representatives belonging to different Sami political parties and Sami stakeholder’s organisations have been interviewed on the field. Moreover, two academic researchers and one public relations officer have also been contacted and interviewed afterwards to offer a different perspective on the topic. The findings of the study indicate that the interviewees have highlighted three main issues while defining the concept of self-determination for indigenous peoples: the importance of recognition and self-identification, the respect of indigenous traditions and the protection of traditional lands. Besides, many ideas mostly based on the development of the Swedish Sami Parliament have also been mentioned while thinking about the future. The study has also shown that the indigenous position in Sweden is quite paradoxical because even if the Sami people have some rights, they do not have self-determination as the current situation is still dominated by the state. Finally, another major aspect of the ...